The Influence of Technological Determinism through Social Media on Farmers' Adoption of Agricultural Innovations - Mariewentty Clarmel Ruhunlela; Mariko Rizkiansyah (Humanities, Society, and Community, 2025)
The agricultural sector has entered the era of Industrial Revolution 4.0, marked by the integration of internet-based technologies such as IoT (Internet of Things) devices and precision farming tools into agricultural practices. This transition offers significant opportunities to enhance community creativity and engagement. This study focuses on Saparua Island in Central Maluku Regency, examining how farmers perceive technological determinism through social media and its impact on agricultural productivity. A qualitative approach was used, employing reception analysis with an encoding-decoding model. Twenty-five respondents were categorized into three positions: dominant, negotiated, and oppositional. The findings reveal diverse public responses to the program "The Future of Farming," which was presented in six segments. The dominant position reflects a positive reception, with participants viewing technology as a beneficial innovation that increases agricultural output, especially for island farmers. Respondents in the negotiated position exhibit mixed reactions, recognizing potential benefits while expressing concerns about the scale of anticipated changes. In the oppositional position, participants resist technological integration, favouring traditional farming methods due to a strong attachment to conventional practices. This study highlights the varied perspectives on technological advancements in agriculture and underscores the importance of addressing these viewpoints to promote a balanced development approach.